Angio-Seal™ Embolization: A Rare Etiology of an Acute Distal Limb Ischemia - Glenmore Lasam; Joshua Brad Oaks; Jeffrey Brensilver (Case Reports in Vascular Medicine)
We herein report a serious vascular complication of diagnostic cardiac catheterization due to an embolization of an Angio-Seal closure device causing acute lower limb ischemia. The Angio-Seal was deployed via the right femoral artery following the catheterization which embolized several hours later to the right popliteal artery. Fogarty embolectomy restored perfusion to the right lower limb; however, compartment syndrome subsequently developed which required evacuation of a hematoma and repair of right popliteal artery.